2004
DOI: 10.1073/pnas.0401553101
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced potentiation of synaptic strength in dopamine neurons: Behavioral correlates in GluRA(–/–) mice

Abstract: Synaptic plasticity in the mesolimbic dopamine (DA) system is thought to contribute to the neural adaptations that mediate behavioral sensitization, a model for core aspects of addiction. Recently, it has been demonstrated that multiple classes of drugs of abuse, as well as acute stress, enhance strength at excitatory synapses on midbrain DA neurons. Here, we show that both the cocaine-and stress-induced synaptic enhancement involves an up-regulation of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 48 publications
12
138
0
Order By: Relevance
“…Recent evidence has shown that blockade of D 1 /D 5 receptor inhibits the AMPAR/NMDAR ratio increase on VTA neurons produced by in vivo cocaine exposure (Dong et al, 2004), supporting our hypothesis for a role of a D 5 -dependent potentiation of NMDARs as a possible mechanism in mediating VTA long-term plasticity produced by cocaine.…”
Section: Discussionsupporting
confidence: 72%
“…Recent evidence has shown that blockade of D 1 /D 5 receptor inhibits the AMPAR/NMDAR ratio increase on VTA neurons produced by in vivo cocaine exposure (Dong et al, 2004), supporting our hypothesis for a role of a D 5 -dependent potentiation of NMDARs as a possible mechanism in mediating VTA long-term plasticity produced by cocaine.…”
Section: Discussionsupporting
confidence: 72%
“…[24][25][26][27][28][29] Previous studies have demonstrated that GluR1 knockout mice (KO) 30 exhibit behavioral abnormalities on tests for cognition, motor function and responses to drugs of abuse. [30][31][32][33][34][35][36][37] In the present study, we sought to extend these data by assessing these mice for a variety of 'schizophrenia-related' phenotypes. In addition, given the wealth of evidence implicating dysfunction of dopamine (DA) neurotransmission in schizophrenia 2 and the major interaction between the dopamine and glutamate systems, 2,38 we evaluated regulation of extracellular striatal DA in GluR1 KO in vivo using high-speed chronoamperometry.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effects of addictive drugs on long-term potentiation (LTP) and long-term depression (LTD) have become a focus of addiction research (Kauer, 2004;Wolf et al, 2004). Dopamine (DA) receptors modulate LTP and LTD in many brain regions important for addiction (Centonze et al, 2003;Jay, 2003;Lovinger et al, 2003), as do DA-releasing psychomotor stimulants such as cocaine (Jones et al, 2000;Thomas et al, 2000Thomas et al, , 2001Ungless et al, 2001;Saal et al, 2003;Dong et al, 2004). However, the mechanisms involved are unclear.…”
Section: Introductionmentioning
confidence: 99%